2009
DOI: 10.1136/vr.164.10.293
|View full text |Cite
|
Sign up to set email alerts
|

Urinary protein:creatinine ratio in rabbits in relation to their serological status to Encephalitozoon cuniculi

Abstract: The concentrations of protein and creatinine were measured in urine samples from 74 healthy domestic pet rabbits, 54 of them seronegative to Encephalitozoon cuniculi and 20 seropositive. The calculated reference range for the urinary protein:creatinine ratio (UPC) of E cuniculi-seronegative rabbits was 0.11 to 0.40. There was no significant variation in the UPC due to the bodyweight, breed, sex, neutered status or husbandry of the rabbits. Seroconversion to E cuniculi was not found to be associated with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
2
23
1
1
Order By: Relevance
“…Specific antibodies develop within 21 days post-infection (11,33). In clinically healthy rabbits, the present study showed that the seropositivity rate for E. cuniculi infection was 49.5%, which is similar to rates (50-53%) of infection in previous studies (6,14,20), although it is higher than the rates of infection reported in some (4,13,17,26,28,(30)(31)(32). In contrast, in the current study, the seropositivity rate of the disease was lower than those previously reported (71-93%) in various countries (3,10,21,37).…”
Section: Discussionsupporting
confidence: 83%
“…Specific antibodies develop within 21 days post-infection (11,33). In clinically healthy rabbits, the present study showed that the seropositivity rate for E. cuniculi infection was 49.5%, which is similar to rates (50-53%) of infection in previous studies (6,14,20), although it is higher than the rates of infection reported in some (4,13,17,26,28,(30)(31)(32). In contrast, in the current study, the seropositivity rate of the disease was lower than those previously reported (71-93%) in various countries (3,10,21,37).…”
Section: Discussionsupporting
confidence: 83%
“…UPCR was fivefold the upper value reported for the species (2.14, reference range 0.11–0.4), but the γ-GT index was within normal limits (Reusch and others 2009, Mancinelli and others 2012). …”
Section: Investigationsmentioning
confidence: 58%
“…Bisher gibt es nur wenige Daten für Kaninchen und Nager. Werte von gesunden Kaninchen lagen, vergleichbar zu Kleintieren, im Bereich von 0,11-0,40 [37]. Rasse, Körpergewicht, Geschlecht und Haltung der Kaninchen hatten keinen Einfluss auf die UPC.…”
Section: Urin-protein-kreatinin-ratio (Upc)unclassified